Bioactive Compounds, Nutritional Traits, and Antioxidant Properties of Artocarpus altilis (Parkinson) Fruits: Exploiting a Potential Functional Food for Food Security on the Comoros Islands - Toilibou Soifoini; Dario Donno; Victor Jeannoda; Ernest Rakotoniaina; Soule Hamidou; Said Mohamed Achmet; Noe Rene Solo; Kamaleddine Afraitane; Cristina Giacoma; Gabriele Loris Beccaro (Journal of Food Quality)
Comoros Union presents a considerable biodiversity of food resources that are neglected or still not valorised, as breadfruit. This study aimed to evaluating nutritional and nutraceutical traits of Artocarpus altilis (Parkinson) Fosberg by characterizing its main bioactive compounds, nutritional traits, and antioxidant properties in order to contribute to the development of traditional and innovative uses of this species as functional food (e.g., infant flour). Bioactive compound composition, antioxidant properties, protein and sugar content, lipids, fibre, and macro- and microelements were observed in these fruits after a specific drying process. Breadfruit showed positive nutritional traits. The main identified phenolic groups were cinnamic acids (with a maximum of 51.88 ± 2.63 mg/100 gDW for chlorogenic acid) and tannins. The highest value of antioxidant activity was 6.40 ± 1.02 mmol·Fe2+/kgDW. This preliminary phytochemical investigation may provide a contribution to the identification and quantification of lead compounds responsible for traditional nutritional and therapeutic claims.